LEGAL IMPLICATIONS OF REGULATIONS CONCERNING LEGAL LIABILITY OF DIRECTORS OF STATE-OWNED ENTERPRISES FOLLOWING THE THIRD AMENDMENT TO LAW NUMBER 19 OF 2003 CONCERNING STATE-OWNED ENTERPRISES - Shafira Sheffy R. R; Reka Dewantara; Amelia Sri Kusuma Dewi (CV. RADJA PUBLIKA, 2025)
The third amendment to Law Number 19 of 2003 concerning State-Owned Enterprises (SOEs) is a response to the need to strengthen state corporate governance and increase the effectiveness of SOEs' role in the national economy. However, this regulatory change also has legal implications for the construction of the legal accountability of SOE directors, particularly in their position as state corporate organs that carry out fiduciary duties but still face the regime of state financial law and criminal law. This study aims to analyse how these regulatory changes affect the limits of directors' responsibility in making business decisions, as well as assess the relevance of applying the business judgment rule principle as an instrument of legal protection for directors. The research method used is normative juridical with a statutory approach, a conceptual approach, and a case approach. The results show that although the legal changes provide reinforcement to the principles of professionalism and independence of directors, there is still a disharmony of norms between the corporate legal regime and the state administrative law regime and criminal law, particularly regarding the interpretation of the element of